2010
DOI: 10.1016/j.rbmo.2009.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene polymorphism and risk of insulin resistance in PCOS

Abstract: The aim of this study was to establish the frequency of angiotensin-converting enzyme (ACE) insertion (I) or deletion (D) gene polymorphism in women with polycystic ovary syndrome (PCOS) and to examine the association of this polymorphism with insulin resistance. A total of 32 women with PCOS and 31 healthy, age- and body mass index-matched controls were studied. Serum lipids, fasting glucose, insulin and other hormones concentrations were measured. Homeostasis model assessment was used to estimate insulin res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 30 publications
3
23
1
Order By: Relevance
“…A meta-analysis by Niu et al 30 showed that the D allele was associated with susceptibility to type 2 diabetes. One study by Celik et al 31 showed that the DD genotype was associated with an increased insulin resistance in women with polycystic ovary syndrome. A study by You et al 32 showed that the D allele was closely associated with reduced highdensity lipoprotein cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Niu et al 30 showed that the D allele was associated with susceptibility to type 2 diabetes. One study by Celik et al 31 showed that the DD genotype was associated with an increased insulin resistance in women with polycystic ovary syndrome. A study by You et al 32 showed that the D allele was closely associated with reduced highdensity lipoprotein cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of an association between ACE I/D polymorphism and PCOS is controversial. Several studies reported no contribution of this polymorphism in susceptibility to PCOS, however, few studies did find a relationship with insulin resistance, hyperandrogenism and aggravated clinical manifestations of PCOS [16][17][18]. A recent meta-analysis by Jia Hongxia et al (2012) reported a significant relation between this polymorphism and PCOS risk in Caucasians but produced a null result for Asians [15].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to assess the possible role of ACE I/D polymorphisms in the aetiopathogenesis of PCOS. [16,18,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 8 studies imported in the meta-analysis, 6 of them had been covered by Jia et al meta-analysis (13)(14)(15)(16)(17)(18). Analyses were performed in 5 different groups of alleles and genotypes including D vs I (Figures 2, 3), DD vs II (Figures 4, 5), DD+DI vs II (Figures 6, 7), DD vs DI+II (Figures 8, 9), and DI vs DD+II (Figures 10, 11).…”
Section: Resultsmentioning
confidence: 99%